Diversity and genetic lineages of environmental staphylococci: a surface water overview. Issue 12 (19th September 2020) - Silva, Vanessa; Caniça, Manuela; Capelo, José L; Igrejas, Gilberto; Poeta, Patrícia
ABSTRACT: Antimicrobial resistance in the environmental dimension is one of the greatest challenges and emerging threats. The presence of resistant bacteria and resistance genes in the environment, especially in aquatic systems, has been a matter of growing concern in the past decade. Monitoring the presence of antimicrobial resistance species, in this particular case, Staphylococcus spp., in natural water environments could lead to a better understanding of the epidemiology of staphylococci infections. Thus, the investigation of natural waters as a potential reservoir and vehicle for transmission of these bacteria is imperative. Only a few studies have investigated the prevalence, antimicrobial resistance and genetic lineages of staphylococci in natural waters. Those studies reported a high diversity of staphylococci species and lineages in surface waters. Methicillin-resistant S. aureus were relatively prevalent in surface waters and, as expected, often presented a multidrug-resistant profile. There was a high diversity of S. aureus lineages in surface waters. The presence of S. aureus CC8 and CC5 suggests a human origin. Among the coagulase-negative staphylococci, the most frequently found in natural waters was S. warneri and S. epidermidis . These studies are extremely important to estimate the contribution of the aquatic environment in the spread of pathogenic bacteria. Abstract : Distribution, diversity and genetic lineages of staphylococci in surface waters.